Increasing the linear dynamic range in LC–MS: is it valid to use a less abundant isotopologue?. Issue 10 (17th April 2017) - Trobbiani, Stephen; Stockham, Peter; Scott, Timothy
Abstract : Liquid chromatography‐mass spectrometry (LC–MS) has quickly become the analytical method of choice in forensic toxicology laboratories due to its ability to detect a very wide range of compounds in a single analysis. One of the major limitations of LC–MS however, is a relatively limited linear dynamic range for quantitation. A new approach to combating this problem is to use the [ +1 M + H] + isotope mass peak for quantitation, thereby reducing saturation at the detector and extending the linear range. This is particularly useful in full‐scan applications, such as quadrupole‐time‐of‐flight (QTOF) mass spectrometry, where the isotopic mass peaks are acquired as a matter of course. Due to the variation in abundance of naturally occurring isotopes for common elements, especially 13 C, this technique has the potential to lead to additional quantitative error. Through a review of published isotope ratio mass spectrometry data, we have assessed this potential for error and found that it is likely to be less than 2% and unlikely to be more than 4%, although this may not apply to compounds containing high numbers of nitrogen or sulphur atoms. This additional potential error must be considered before using this technique as it may not be appropriate for all applications. We have deemed it fit for purpose for our application and demonstrate the applicability of this technique to a quantitative LC‐TOF method. © 2017 Commonwealth of Australia. Drug Testing and Analysis © 2017 John Wiley & Sons, Ltd. Abstract : The use of a less abundant isotopologue for quantitation in LC–MS is a simple way to extend the linear dynamic range of a method, especially for high‐resolution mass spectrometers. However it may also increase the quantitative error. The likely magnitude of this error was assessed by reviewing the scientific literature for published isotope ratios and the technique was applied to a quantitative LC‐TOF method.